An equity lens on behavioral science for conservation. Issue 5 (28th April 2022) - Crosman, Katherine M.; Jurcevic, Ines; Van Holmes, Carlin; Hall, Crystal C.; Allison, Edward H.
Abstract: In recent decades, interest in and application of behavioral insights to conservation theory and practice have expanded significantly. Yet the growth of integrated strategies to adapt and guide human behavior in service of conservation outcomes has included limited engagement with questions of equity and power. Here we examine the use of behavioral approaches in conservation efforts, emphasizing potential misapplications that may result from omitting equity and power considerations. Such omission may lead to an overemphasis on the role of individual behaviors relative to system‐level drivers of biodiversity loss, result in misalignment between behavioral interventions and the actual drivers of behavior in situ, and incur unanticipated negative social welfare and distributional costs, all of which may undermine conservation success. We offer recommendations for centering equity when applying behavioral insights to conservation, including strategies for high‐level agenda setters (scholars, advocates, funders and programmatic leaders) as well as conservation practitioners. The urgent need for biodiversity conservation is insufficient reason to side‐step equity and power considerations; we contend that centering equity is consistent with this urgency and key for developing sustainable conservation theory and practice.